Solve all your doubts with Teachoo Black (new monthly pack available now!)

Are you in **school**? Do you **love Teachoo?**

We would love to talk to you! Please fill this form so that we can contact you

Miscellaneous

Misc 1
Deleted for CBSE Board 2023 Exams
You are here

Misc 2 Deleted for CBSE Board 2023 Exams

Misc 3 Important Deleted for CBSE Board 2023 Exams

Misc 4 Deleted for CBSE Board 2023 Exams

Misc 5 Deleted for CBSE Board 2023 Exams

Misc 6 Important Deleted for CBSE Board 2023 Exams

Misc 7 Important

Misc 8

Misc 9

Misc 10 Important

Misc 11

Misc 12

Misc 13

Misc 14 Important

Misc 15 Deleted for CBSE Board 2023 Exams

Misc 16 Important Deleted for CBSE Board 2023 Exams

Misc 17

Misc 18

Misc 19 Important

Misc 20

Misc 21 (i) Important Deleted for CBSE Board 2023 Exams

Misc 21 (ii) Deleted for CBSE Board 2023 Exams

Misc 22 Important Deleted for CBSE Board 2023 Exams

Misc 23 Important Deleted for CBSE Board 2023 Exams

Misc 24 Deleted for CBSE Board 2023 Exams

Misc 25 Important Deleted for CBSE Board 2023 Exams

Misc 26 Deleted for CBSE Board 2023 Exams

Misc 27 Deleted for CBSE Board 2023 Exams

Misc 28 Important Deleted for CBSE Board 2023 Exams

Misc 29 Important

Misc 30 Deleted for CBSE Board 2023 Exams

Misc 31 Important

Misc 32 Important Deleted for CBSE Board 2023 Exams

Last updated at May 29, 2018 by Teachoo

Misc 1 Show that the sum of (m + n)th and (m – n)th terms of an A.P. is equal to twice the mth term. First we calculate (m + n)th , (m – n)th and mth terms of an A.P We know that an = a + (n – 1)d Where an is nth term of AP a be the first term & d be the common difference of the A.P. For (m + n)th term putting n = m + n in (1) am + n = a + (m + n – 1)d For (m – n)th term putting n = m – n in (1) am – n = a + (m – n – 1)d for mth term putting n = m in (1) am = a + (m – 1)d We need to prove Sum of (m + n)th term & (m – n)th terms is twice of mth term i.e. am + n + am – n = 2am Taking L.H.S am + n + am – n = a + (m + n – 1)d +[a + (m – n – 1)d] = a + a + (m + n – 1)d + (m – n – 1)d] = 2a + (m + n – 1 + m – n – 1 )d = 2a + (m + m – 1 – 1 + n – n)d = 2a + (2m – 2 – 0)d = 2a + 2(m – 1)d = 2[a + (m – 1)d] = 2am = R.H.S Hence L.H.S = R.H.S Hence proved